Analisis ANALISIS IMPLEMENTASI PEMBELAJARAN PROJECT BASED LEARNING DALAM MUATAN IPA DI KELAS 5 SEKOLAH DASAR - Ramadani, Merlisa; Faizal Chan; Violita Zahyuni (Jurnal Tunas Pendidikan, 2024)
This research aims to describe the implementation of Project Based Learning (PjBL) model learning on science content in class 5 of Muara Bulian State Elementary School 13/I. It is hoped that the results of this research can be used as a source of information regarding the implementation of the Project Based Learning (PjBL) learning model in science content in class 5 of the state elementary school 13/I Muara Bulian. Based on the results of the research and discussion, it can be concluded that the analysis of the implementation of project-based learning in science content in class 5 of Muara Bulian State Elementary School 13/I carried out by the class 5C teacher in the material "Seeing because of Light, Hearing because of Sound" can increase student learning activities and are carried out based on the five steps of PjBL learning, namelyStart with the Essential Question, Design a Plan for the Project, Create a Schedule, Monitor the Students and the Progress of the Project, Assess the Outcome, dan Evaluate the Experience.